Atmospheric CO2 sequestration in iron and steel slag: Consett, Co. Durham, UK - Mayes, William M.; Riley, Alex L.; Gomes, Helena I.; Brabham, P.; Hamlyn, J.; Pullin, H.; Renforth, P. (ACS Publications, 2018)
Carbonate formation in waste from the steel industry could constitute a non-trivial proportion of global requirements to remove carbon dioxide from the atmosphere at potentially low cost. To constrain this potential, we examined atmospheric carbon dioxide sequestration in a >20 million tonne legacy slag deposit in northern England, UK. Carbonates formed from the drainage water of the heap had stable carbon and oxygen isotope values between -12 and -25 ‰ and -5 and -18 ‰ for δ13C and δ18O respectively, suggesting atmospheric carbon dioxide sequestration in high pH solutions. From the analyses of solution saturation states, we estimate that between 280 and 2,900 tCO2 have precipitated from the drainage waters. However, by combining a thirty-seven-year dataset of the drainage water chemistry with geospatial analysis, we estimate that <1 % of the maximum carbon capture potential of the deposit may have been realised. This implies that uncontrolled deposition of slag is insufficient to maximise carbon sequestration, and there may be considerable quantities of unreacted legacy deposits available for atmospheric carbon sequestration.